Aiming High Indonesia's Ambition to Reduce Stunting - Rokx, Claudia (World Bank E-Library Archive, 2018)
In the 1980's Indonesia became an example for other countries concerned with reducing high levels of malnutrition. At the time, Indonesia had started nutrition programming and surveillance at the village level using the integrated weighing and child health posts, or Posyandu. In the ensuing decades there have been successes: small scale and bigger scale interventions that reduced malnutrition. At the same time, there have been set-backs, loss of attention, other priorities, decentralization, weak management and poor governance. In August 2017, the Indonesian government unveiled a new strategy to accelerate reductions in rates of stunting. This book looks at what will be required to turn that strategy - the National Strategy to Accelerate Stunting Prevention (StraNas Stunting) 2017-2021 - from vision into reality. It looks at the country's ambitious reforms and goals to reduce stunting. It examines the government's plans to boost awareness about the economic, social and personal cost of stunting, to ensure a truly national "multi-sectoral" effort to tackle the problem at scale in a coordinated and cohesive fashion in communities across Indonesia. It chronicles past successes and setbacks, drawing lessons from them about the future. We think Indonesia is on a path towards new success: this time at scale. It is a story worthtelling